Including the excluded : from practice to policy in European community development - Henderson, Paul, 1942- (Policy Press ; Combined European Bureau for Social Development (CEBSD), 2005)
This book provides an in-depth study of how community development can contribute to tackling social exclusion. Examples from policy and practice in the UK, Spain, Belgium, Sweden and Norway are discussed, with additional information from Denmark, Ireland and Hungary.